2019
DOI: 10.1016/j.jcsr.2019.105741
|View full text |Cite
|
Sign up to set email alerts
|

In-plane bending behaviour and capacities of S690 high strength steel welded I-section beams

Abstract: The present paper describes an in-depth experimental and numerical investigation into the inplane flexural behaviour and bending moment resistances of S690 high strength steel welded I-section beams. The experimental investigation was conducted on six different welded Isections fabricated from the same batch of 5 mm thick S700MC high strength steel hot-rolled plated by means of gas metal arc welding, and involved initial local geometric imperfection measurements and twelve in-plane four-point bending tests, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 29 publications
(35 reference statements)
3
33
0
1
Order By: Relevance
“…Fig. 6 displays the fourpoint bending test setup, in which the beam specimen is simply supported between two steel rollers while a spreader beam is utilised to transfer load at the third-points of the flexural span between the two steel rollers [20][21][22][23], underpinning bolts (inserted between the inner faces of the two flanges) are used together with G-clamps (clamped onto the outer faces of the flanges) at the two supports and two loading points for the purpose of precluding local bearing and crushing failure at these positions, and three line transducers are arranged below the channel section beam specimen to measure the vertical deflections at the mid-span and two loading points. The readings from the three line transducers were used to derive the curvature of the constant moment span between the loading points κ through Eq.…”
Section: Four-point Bending Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fig. 6 displays the fourpoint bending test setup, in which the beam specimen is simply supported between two steel rollers while a spreader beam is utilised to transfer load at the third-points of the flexural span between the two steel rollers [20][21][22][23], underpinning bolts (inserted between the inner faces of the two flanges) are used together with G-clamps (clamped onto the outer faces of the flanges) at the two supports and two loading points for the purpose of precluding local bearing and crushing failure at these positions, and three line transducers are arranged below the channel section beam specimen to measure the vertical deflections at the mid-span and two loading points. The readings from the three line transducers were used to derive the curvature of the constant moment span between the loading points κ through Eq.…”
Section: Four-point Bending Testsmentioning
confidence: 99%
“…The shell element S4R, having been extensively used by the authors in the numerical simulations of thin-walled steel open section structural members under various loading conditions [12,15,[18][19][20][21]26,27], was adopted in the present finite element modelling of pressbraked S690 high strength steel channel section beams. The mesh size was selected to be equal to the wall thickness t of the modelled channel section for the flat regions while a finer mesh of four elements was used to discretise the corner portions of the cross-section to capture the rounded geometric profiles, following a prior mesh sensitivity study taking into account both the numerical accuracy and computational efficiency.…”
Section: Development and Validation Of Fe Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al [3] and Rasmussen and Hancock [4] performed concentric compression tests on S690 high strength steel welded I-section stub columns, quantified their cross-section compressive resistances and evaluated the accuracy of the relevant codified design rules on slenderness limits and effective element widths. The flexural behaviour and strengths of S690 high strength steel welded I-section beams bent about both the major and minor principal axes were experimentally and numerically examined by Wang [5] and Sun et al [6], with the codified slenderness limits and design flexural strengths assessed. A series of experimental and numerical studies on S690 high strength steel welded I-section columns [7][8][9] and beam-columns [10] were performed to respectively investigate their member stability in pure compression and combined compression and bending moment, and on the basis of the experimental and numerical results, the relevant design provisions prescribed in the existing design standards were examined, followed by the development of new design proposals.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the experimentally and numerically obtained results were employed to assess the accuracy of the existing slenderness limits and local buckling design rules for S690 high strength steel welded I-section stub columns and beams, as set out in the European code EN 1993-1-12 (CEN, 2007, American specification ANSI/AISC 360-16 (AISC, 2016) and Australian standard AS 4100 (AS, 2016). The findings of this research work have been reported in Sun et al (2019aSun et al ( , 2019b.…”
Section: Introductionsupporting
confidence: 62%